Perplexity in Accounting Conservatism: a Critical Review - Fatchan, Fuad Hudaya; Widagdo, Ari Kuncara (Universitas Muhammadiyah Surakarta, 2021)
This paper aims to provide an overview of the literature regarding the definition of accounting conservatism, review literature evidence on the interpretation and role of accounting conservatism and determine the factors that influence conservatism at the company level and the country level. This study shows that the debate about accounting conservatism is largely driven by confusion about the definition and interpretation of conservatism. It is important for researchers to distinguish between the two types of conservatism and to adopt appropriate measures and theories in future research.